A proposed de-noising algorithm - Abdulwahab, Nawafil; Alshaikhli, Imad Fakhri Taha (IIUM, 2020)
Minimizing noises from images to restore it and increase its quality is a crucial step. For this, an efficient algorithm was proposed to remove noises such as (salt pepper, Gaussian, and speckle) noises from grayscale images. The algorithm did that by selecting a window measuring 3x3 as the center of processing pixels, other algorithms did that by using median filter (MF), adopted median filter (AMF), adopted weighted filter (AWF), and the adopted weighted median filter (AWMF). The results showed that the proposed algorithm compared to previous algorithms by having a better signal-to-noise ratio (PSNR).